Sistem Penyiram Tanaman Yang Dapat DimonitorDengan Komputer Dan Perangkat Mobile - Widiharto, Widiharto, Dr. Heru Supriyono, M.Sc (2017)
Curently most monitoring plant watering is still done by hand. It has several deficiencies, including needs more manpower to monitor growth and development of plants that actualy adds to the cost of care, they still lack the knowladge of farmers about soil moisture and air emperature. Based on this, the authors innovate to create a models automatic watering which can be monitored via the computer and mobile devices as an interfaces with the website. The purpose of this study is to provide ease of monitoring performed by the automatic watering system. The results of these watering displayed through tables and graphs watering . Arduino UNO is used as the main component, is used to control the water pump and heating lamps simulated with Light Emitting Diode (LED). DHT11 air temperature sensor and soil moisture sensors Flying-Fish used to detect temperature and soil humidity. Table watering can also be printed in the document file. From the reusults, the average difference DHT11 sensor with tool laboratorium is 0,62°C and the average defference sensore with tools Flying-Fish laboratorium is 4,6%. The website for monitoring automatic watering is going well. All automatic watering activity able to be displayed accurately by the website through tables and graphs watering.